Parents and Students in Educational Services with Special Reference to Tutoring & Online Courses - Parag Kalkar, V. Ambedkar, Manish Didwania, Suresh Frederick, N.V.S.Suryanarayana (Journal of Informatics Education and Research, 2024)
The growing use of technology into classrooms has caused major changes in the educational landscape in recent years. With traditional tutoring services and online courses playing a crucial part in bolstering students' academic success, the move toward digital platforms has completely changed how students obtain education. The study "Parents and Students in Educational Services with Special Reference to Tutoring & Online Courses" examines how educational services are changing and how they affect the lives of parents and students. This study intends to offer important insights into how tutoring and online courses affect academic achievement and general pleasure by concentrating on the preferences and experiences of parents and students. Several statistical tests were performed on a sample of 76 respondents to investigate the connections among academic success, parental satisfaction, and the type of educational service.